Effects of Wood Species and Log Diameter on Veneer Recovery - B. Kewilaa (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
The total plywood production depends on veneer production due to log consumption. The ratio of veneer volume to log volume was stated as veneer recovery. The veneer recovery was affected by wood species and log diameter. Three wood species of Shorea selanica, Terminalia catapa and Duabanga moluccana were used in this experiment with four levels of log diameters. This experiment used the split block design and orthogonal polynomial analyses for equal space. The statistical analysis shows that wood species, log diameter and their interaction gave significance to highly significant effects on veneer recovery. The regression model for effect of log diameter (X) on veneer recovery (Y) by orthogonal polynomial analysis was Y = 34.373+ 0.429 X, with R2 = 0.7366